TREATMENT OF ORAL LEUKOPLAKIA WITH ANTIOXIDANTS – A SYSTEMATIC REVIEW - T.N. UMA MAHESWARI (International Journal of Pharma and Bio Sciences, 2013)
Oral leukoplakia is one of the common potentially malignant disorder which is mostly associated with the use of tobacco either in the form of smoking or smokeless, though idiopathic leukoplakia in patients free from habits has also been reported. Diagnosis of the lesion in most of the cases is mainly based on history of use of tobacco and clinical finding such as raised elevated non-scrap able white patch seen in oral mucosa. Oral leukoplakia once diagnosed, the patient is advised to discontinue the habit after proper counselling of the risk of leukoplakia turning into malignancy and is supported with mainly antioxidants in mild cases. There are few clinical trials using other non surgical management like topical bleomycin, laser therapy, photodynamic therapy etc., but use of antioxidants is more common. This review article aims in evaluating all the clinical trials using antioxidants namely Vitamin A,E,C, and lycopene as they are the most commonly used antioxidants in treatment of oral leukoplakia to assess the outcome measures such as clinical resolution, adverse effects, recurrence and malignant transformation.